Detection and Prevention of Phishing Attack Using Linkguard Algorithm - Akinyede, Raphael Olufemi; Adelakun, Joseph Adebowale; Olatunde, Kemi Victoria (Journal of Information, 2018)
Phishing is another sort of network attack where the attacker creates an imitation of a current site page to trick users into submitting individual, financial related, or password information to what they believe is their service provider’s site. The idea is an end-host based anti-phishing algorithm, called the Link Guard, by using the generic attributes of the hyperlinks in phishing attacks. The link Guard algorithm is the idea for finding the phishing electronic messages sent by the phisher to get hold on the data of the end user. Link Guard depends on investigation of the attributes of phishing hyperlinks. Each end user is implemented with Link Guard algorithm. Subsequent to doing as such, the end user perceives the phishing emails and can abstain from responding to such mails. Since Link Guard is qualities based, it can identify and prevent not only known phishing but also obscure ones.